Práticas de enfermagem na prevenção da pneumonia associada à ventilação mecânica na terapia intensiva neonatal - Silva, Paula Isis Nascimento (2020)
Ventilator-Associated Pneumonia in the newborn is considered as a Health Care-Related Infection associated with mechanical ventilation for more than two days or detection of infection 24 hours after discontinuation of therapy. Technological advancement has increased the newborn's survival, however, the use of the mechanical ventilator has been associated with the occurrence of adverse events, such as Pneumonia Associated with Mechanical Ventilation. Thus, the prevention of these infections has been a challenge to guarantee the quality of care in health services. This research aims to analyze nursing practice in the context of factors related to the occurrence of Pneumonia Associated with Mechanical Ventilation to propose a care product capable of improving measures to prevent this infection. It is a Convergent Care Research, with quantitative and qualitative approaches, carried out in a Neonatal Intensive Care Unit of a maternity school, from December 2019 to September 2020. 19 nurses, 39 nursing technicians and 07 managers participated in the study. The four methodological phases of Convergent Care Research were followed: conception, instrumentation, scrutiny and analysis. Data collection was carried out through three stages: verification of nursing knowledge and practices, survey of data on the incidence of Pneumonia Associated with Mechanical Ventilation and individual interviews. Quantitative data were organized in Excel spreadsheets and analyzed according to descriptive statistics. Qualitative data were organized using the qualitative analysis software, Atlas ti, and analyzed following the steps of apprehension, synthesis, theorization and transfer. In the process of recognizing preventive measures and care practices that compromised the safety of neonatal patients, solutions and coping measures were revealed, such as an adequate number of professionals, provision of materials and supplies, management supervision and support, permanent education and use of protocols assistance. With the categorization of data from the interviews with managers, two categories were elucidated: Factors for the occurrence of Pneumonia Associated with Mechanical Ventilation in neonates and Nursing practices for the prevention of Pneumonia Associated with Mechanical Ventilation in neonates. This categorization enabled theorizing, which shows that this infection is revealed as a problem that needs to be solved through care and management practices, for prevention to occur effectively. Based on this, assistive technological products were elaborated, namely: primer with diagnostic situation for managers, Standard Operating Procedure for the prevention of Pneumonia Associated with Mechanical Ventilation in newborns and implementation flowcharts and monitoring of adherence to preventive measures and results achieved. The Standard Operating Procedure was chosen from among the tools suggested by managers, as it presents good acceptance and applicability in the institution. With the implementation of this product and following the flowcharts, it will be possible to follow the necessary path for adherence to prevention measures to be effective and to improve care, causing an impact in reducing the incidence of Pneumonia Associated with Mechanical Ventilation. It is also expected that, with the necessary support, there will be a change in the behavior of the nursing team and that management will continue to develop policies that ensure the safety of the neonate patient.